2020
DOI: 10.1016/j.amsu.2019.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal hernias in cirrhotic patients: Surgery or conservative treatment? Results of a prospective cohort study in a high volume center: Cohort study

Abstract: BackgroundSurgical treatment of abdominal hernias in cirrhotics is often delayed due to the higher morbidity and mortality associated with the underlying liver disease. Some patients are followed conservatively and only operated on when complications occur (“wait and see” approach). The aim of this study is to compare outcomes of cirrhotic patients undergoing conservative non-operative care or elective hernia repair.MethodsA prospective observational study including 246 cirrhotic patients with abdominal hernia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
5
12
0
Order By: Relevance
“…Regarding sex, the group of patient with cirrhosis had a higher prevalence of men (76%) than non-cirrhotic patient, similar to that found by Pinheiro et al [ 13 ] who only analyzed a population of patients with hernia and cirrhosis (73.9%). The BMI of patients with cirrhosis (26.2) in our study was lower than that found in the group without cirrhosis, probably due to the state of malnutrition resulting from cirrhosis.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Regarding sex, the group of patient with cirrhosis had a higher prevalence of men (76%) than non-cirrhotic patient, similar to that found by Pinheiro et al [ 13 ] who only analyzed a population of patients with hernia and cirrhosis (73.9%). The BMI of patients with cirrhosis (26.2) in our study was lower than that found in the group without cirrhosis, probably due to the state of malnutrition resulting from cirrhosis.…”
Section: Discussionsupporting
confidence: 83%
“…[8] For these reasons, in addition to the supposed perioperative decompensation, the repair of hernias in the abdominal and inguinal wall in these patients is traditionally managed by a “watch and see strategy.” [5,8–12] However, this strategy can lead to worse outcomes for the patient in inadequate clinical conditions, such as in emergency cases, where an increased risk of perioperative morbidity and mortality is frequently found. [13–15]…”
Section: Introductionmentioning
confidence: 99%
“…The increased postoperative mortality associated with DC is in line with prior studies that stratified the preoperative populations according to escalating levels of MELD and Child-Pugh scores [4,11]. These studies showed a correlative risk in postoperative mortality with rising scores, thus reinforcing the importance of liver prognostication in these select patients with underlying cirrhosis [4,11,31,32]. Our study supports these conclusions, as it demonstrates a similar rise in risk ratios (odds ratios and adjusted odds ratios) associated with DC, although this was only evident in patients undergoing umbilical and other abdominal hernia repairs.…”
Section: Discussionsupporting
confidence: 81%
“…These studies may not be applicable to current hernia repair outcomes in cirrhotic patients since they are over a decade old [4,7–10,12]. Additionally, many of these studies are cohort-based studies with a small sample size, which further reduces their statistical power [4,8–10,12]. Therefore, in order to better clarify the current prognostic implications of cirrhosis on hernia repair outcomes, there needs to be a study approach that incorporates a large-scale database with current data on the intersection between cirrhosis and various types of hernia surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a conservative approach can also be accompanied by severe complications; our study showed more incarceration, decompensated cirrhosis, and ultimately death for the patients in the conservative treatment group than in the intervention group. Other authors describe a nearly 23% emergency surgery rate due to complications of a hernia during conservative treatment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%